A Linear Curve Fit Analysis of FDI Flows in Selected Sectors in India - Sujatha, L.; Ganesh Kumar, Radha (International Journal of Psychosocial Rehabilitation, 2019)
This paper attempts to analyze foreign direct investment flows in three selected sectors, such as service, telecommunication, and drug and pharmaceutical industries. An analytical research is attempted to investigate the minimum, maximum, mean, and standard deviation of FDI flows in the years 2010-2015. A linear fit has also been done for the FDI flows. Suitable suggestions are given based on flows in selected sectors.